Rhetoric and Recollection: Recounting the George W. Bush Administration's Case for War in Iraq. Issue 1 (28th July 2017) - Bahador, Babak; Moses, Jeremy; Lafi Youmans, William
Abstract : President George W. Bush and his administration presented a variety of justifications for the 2003 Iraq war. Academic literature and journalism about the communication campaign emphasized two reasons: Iraq's alleged weapons of mass destruction program and links to terrorism. Drawing on the first systematic content analysis of the administration's official speeches and statements, this study recounts a more complex, changing campaign with surprising findings. Other justifications, such as international law, human rights, and freedom, were at times more common than the most recalled reasons. This article also explores individual officials' arguments and changes over time in response to key events.